Round table. Importance and indications of the uroradiological study in general surgery. Introduction - Lorenzo, Juan C; Zubiaurre, Leandro (Cirugía del Uruguay, 1971)
The interpretation that was produced of these procedures is closely linked to their technical knowledge. For this reason, from a technological point of view, Radiology is a specialty that has perfectly defined borders that are the domain of the radiologist. From the point of view of interpretation we said that the borders are less precise, because it cannot be argued that the urologist in this case has the capacity, of course, to judge the radiological documents that are produced by a Department of Radiology.